The Role of Ultrasonographic Biomicroscopy in the management of a patient with presumed Dematiaceous Mycotic Keratitis - ISPUB - Tan , A.K; Premsenthil, P.S; Aziz, A.; Asok, T.; G, Intan (The Internet Journal of Ophthalmology and Visual Science, 2009)
We report the use of Ultrasonographic Biomicroscopy in the management of a patient with presumed dematiaceous mycotic keratitis.